IL-17 Genetic and Immunophenotypic Evaluation in Chronic Graft-versus-Host Disease - Renata Gonçalves Resende; Jeane de Fátima Correia-Silva; Tarcília Aparecida Silva; Ulisses Eliezer Salomão; Luciano Marques-Silva; Érica Leandro Marciano Vieira; Walderez Ornelas Dutra; Ricardo Santiago Gomez (Mediators of Inflammation)
Although interleukin-17 (IL-17) is a recently discovered cytokine associated with several autoimmune diseases, its role in the pathogenesis of chronic graft-versus-host disease (cGVHD) was not established yet. The objective of this study was to investigate the association of IL17A and IL17F genes polymorphisms and IL-17A and IL-17F levels with cGVHD. IL-17A expression was also investigated in CD4+ T cells of patients with systemic cGVHD. For Part I of the study, fifty-eight allo-HSCT recipients and donors were prospectively studied. Blood samples were obtained to determine IL17A and IL17F genes polymorphisms. Cytokines levels in blood and saliva were assessed by ELISA at days +35 and +100 after HSCT. In Part II, for the immunophenotypic evaluation, eight patients with systemic cGVHD were selected and the expression of IL-17A was evaluated. We found association between recipient AA genotype with systemic cGVHD. No association was observed between IL-17A levels and cGVHD. Lower IL-17A levels in the blood were associated with AA genotype. In flow cytometry analysis, decreased expression of IL-17A was observed in patients with cGVHD after stimulation. In conclusion, IL-17A may have an important role in the development of systemic cGVHD.